The iron records and its sources during 1990–2017 from the Lambert Glacial Basin shallow ice core, East Antarctica. (July 2020) - Du, Zhiheng; Xiao, Cunde; Mayewski, Paul A.; Handley, Mike J.; Li, Chuanjin; Ding, Minghu; Liu, Jingfeng; Yang, Jiao; Liu, Ke
Abstract: In this study, a shallow ice core (12.5 m, called LGB) was drilled at the Lambert Glacial Basin, East Antarctica. The major ion and metal elements were measured at 5–6 cm resolution in this shallow core, which covered the period 1990–2017. Therefore, an annual-resolution record of iron (Fe) concentrations and fluxes were reconstructed in this shallow ice core. Although the Fe data is comparable to previous results, our results emphasized that much more dissolved Fe (DFe) from the Cerro Hudson volcanic event (August 1991) was transported to the East Antarctic ice sheet, in comparison with the Pinatubo volcanic event (June 1991). The aeolian dust may be the primary DFe source during 1990–2017. In particular, the DFe variations may be affected by the biomass burning emissions in two periods (1990–1998 and 2014–2017). While total dissolved Fe (TDFe) variations were controlled by the climatic conditions since 2000 because of the temperature (δ 18 O) decreasing at East Antarctica. These Fe data will be useful to assess the modern bioavailable Fe release for the Antarctica ice sheet. Highlights: High resolution DFe (TDFe) data was collected from an East Antarctic shallow core. The eruption events can provide plenty DFe and stored in Antarctica ice sheet. Fe variations during 1990–2017 were controlled by natural climatic characteristics.